Twenty-eight-day repeated oral doses of sodium valproic acid increases neural stem cells and suppresses differentiation of granule cell lineages in adult hippocampal neurogenesis of postpubertal rats. (15th September 2019) - Watanabe, Yousuke; Nakajima, Kota; Ito, Yuko; Akahori, Yumi; Saito, Fumiyo; Woo, Gye-Hyeong; Yoshida, Toshinori; Shibutani, Makoto
Highlights: Effect of 28-day VPA treatment on hippocampal neurogenesis was examined in rats. VPA increased neural stem cells accompanying SCF-KIT signaling and BTG2 response. VPA suppressed neurodifferentiation accompanying interneuron and BTG2 responses. Disruption pattern of neurogenesis was different from developmental VPA exposure. Disruptive neurogenesis can be detected by 28-day treatment of postpubertal rats. Abstract: Developmental exposure to valproic acid (VPA), a model compound for experimental autism, has shown to primarily target GABAergic interneuron subpopulations in hippocampal neurogenesis of rat offspring. The VPA-exposed animals had revealed late effects on granule cell lineages, involving progenitor cell proliferation and synaptic plasticity. To investigate the possibility whether hippocampal neurogenesis in postpubertal rats in a protocol of 28-day repeated exposure is affected in relation with the property of a developmental neurotoxicant by developmental exposure, VPA was orally administered to 5-week-old male rats at 0, 200, 800 and 900 mg/kg body weight/day for 28 days. At 900 mg/kg, GFAP + cells increased in number, but DCX + cells decreased in number in the granule cell lineages. Moreover, CHRNB2 + cells and NeuN + postmitotic neurons decreased in number in the hilus of the dentate gyrus. Transcript level examined at 900 mg/kg in the dentate gyrus was increased with Kit, but decreased with Dpsyl3, Btg2, Pvalb and Chrnb2 . These results suggest that VPA increased type-1 stem cells in relation to the activation of SCF-KIT signaling and suppression of BTG2-mediated antiproliferative effect on stem cells. VPA also decreased type-3 progenitor cells and immature granule cells probably in relation with PVALB + interneuron hypofunction and reduced CHRNB2 + interneuron subpopulation in the hilus, as well as with suppression of BTG2-mediated terminal differentiation of progenitor cells. Thus, the disruption pattern of VPA by postpubertal exposure was different from developmental exposure. However, disruption itself can be detected, suggesting availability of hippocampal neurogenesis in detecting developmental neurotoxicants in a 28-day toxicity study.